Critical success factors for building information modelling BIM implementation for power plant projects in Malaysia - Aziz, Mohd Azrul; Chee, Fui Wong; Haron, Nuzul Azam; Ales @ Alias, Aidi Hizami; Raja Ahmad Effendi, Raja Ahmad Azmeer; Ooi, Kuan Tan (Kulliyah of Engineering, International Islamic University Malaysia, 2022)
Building Information Modelling (BIM) has become increasingly important for the construction industry in Malaysia. BIM implementation process requires proper strategic planning and considerations from many aspects.Malaysian government has realised the importance of BIM as an emerging technology to transform the construction industry in Malaysia,and thus has classified BIM as one of the twelve main technology in CIDB “Construction 4.0 Strategic Plan 2021-2025”. BIM implementation offer significant benefits to the power generation sector in Malaysia Thisstudy was conducted using the quantitaive research method in which questionnaires survey were distributed to the clients‘ representatives in the Malaysian power sector. This study has identified the 13 critical success factors to be considered by clients for BIM implementation in power plant projects in Malaysia. The success factors were classified based on the four (4) main fields or factors namely management, people, process and technology. The study findings show that management support is the most important success factor for the power plant projects while other success factors such as people, process and technology were also identified and discussed.